Risk Factors for Preoperative Anxiety and Depression in Patients Scheduled for Abdominal Aortic Aneurysm Repair - Xiao-Yan Liu; Yu-Kui Ma; Ji-Chun Zhao; Zhou-Peng Wu; Lin Zhang; Li-Hui Liu (Chinese Medical Journal, 2018)
Background: Perioperative emotional disorders of patients underwent abdominal aortic aneurysm (AAA) repair is an emerging area of study, and preoperative mental distress of those patients remains poorly understood. The aim of this study was to investigate the prevalence and identify the risk factors of preoperative anxiety and depression in patients scheduled for AAA repair. Methods: A total of 189 patients who underwent elective AAA repair between 2015 and 2016 were included in this study. These patients were preoperatively evaluated by Hospital Anxiety and Depression Scale (HADS). Demographics and anxiety and depression scores of the patients were documented. Logistic regression was used to identify the independent risk factors of preoperative anxiety and depression. Results: A total of 150 AAA patients were included in final analysis. Of these 150 patients, 44 patients (29.3%) had borderline anxiety or clinical anxiety, and 42 patients (28.0%) were found to have borderline or clinical depression. Female (odds ratio [OR]: 2.81, 95% confidence interval [CI]: 1.08–7.26), the American Society of Anesthesiologists (ASA) Grade 3/4 (OR: 4.34, 95% CI: 1.13–16.68), higher education (OR: 1.44, 95% CI: 1.02–2.04), and abdominal or back pain (OR: 3.08, 95% CI: 1.20–7.87) were identified as significant independent risk factors of abnormal HADS-anxiety in overall patients; and higher level of education (OR: 1.87, 95% CI: 1.16–3.01) was predictive of anxiety in patients planned for endovascular aortic repair. Besides, higher body mass index (BMI) (OR: 1.18, 95% CI: 1.04–1.33) and abdominal or back pain (OR: 3.93, 95% CI: 1.70–9.11) were predictive of abnormal preoperative HADS-depression in overall patients. Conclusion: As for patients scheduled for AAA repair, female, higher ASA, higher level of education, and symptom may be independent risk factors for preoperative anxiety, and symptom and higher BMI may predict preoperative depression.